1992
DOI: 10.1016/s0266-7681(05)80238-4
|View full text |Cite
|
Sign up to set email alerts
|

Is Early Vascularization of Nerve Grafts Necessary?

Abstract: Revascularization and regeneration through vascularized and non-vascularized nerve grafts were compared on optimal and adverse graft beds in 76 rabbit sciatic nerves. A delay in revascularization of more than 14 days was found to occur in 30 mm long, non-vascularized nerve grafts placed on completely avascular graft graft beds. However, over a period of 44 weeks, this prolonged ischaemia did not adversely affect nerve regeneration. The vascularized nerve grafts did not differ significantly with respect to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 13 publications
0
13
1
Order By: Relevance
“…Many authors have demonstrated various similarities and differences between vascularized and nonvascularized grafts. [22][23][24][25][26][27] The most recognizable might be that the number of regenerating axons and the regeneration velocity do not differ between the two methods, even when the graft was placed into avascular tissue. 25 Our previous results on the different expression of E and N cadherins between the two methods failed to explain these identical findings regarding axonal regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have demonstrated various similarities and differences between vascularized and nonvascularized grafts. [22][23][24][25][26][27] The most recognizable might be that the number of regenerating axons and the regeneration velocity do not differ between the two methods, even when the graft was placed into avascular tissue. 25 Our previous results on the different expression of E and N cadherins between the two methods failed to explain these identical findings regarding axonal regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 However, Mani et al did not find any significant difference between vascularized and nonvascularized nerve grafts in avascular graft beds, even after prolonged initial period of revascularization for nonvascularized nerve grafts. 32 Normal recipient bed experimental studies are conflicted as to which produces the best results: Restrepo et al, 33 Shibata et al, 34 Kanaya et al, 35 and Schultes et al 36 reported better results with vascularized nerve grafts, whereas McCullough et al, 37 Pho et al, 38 and Seckel et al 39 did not find any difference.…”
Section: Vascular Supply Of the Recipient Bedmentioning
confidence: 99%
“…In a nonvascularized nerve graft (NVNG), neovascularization, the onset of new blood vessel formation at the interface with host tissue, usually occurs by the third day after surgery under supportive conditions (Mani et al, ). Conversely, neovascularization in VNGs can occur before the onset of ischemia, due to the presence of vascular structures within the graft (Mani et al, ).…”
Section: Vascularized Nerve Graftsmentioning
confidence: 99%
“…In a nonvascularized nerve graft (NVNG), neovascularization, the onset of new blood vessel formation at the interface with host tissue, usually occurs by the third day after surgery under supportive conditions (Mani et al, ). Conversely, neovascularization in VNGs can occur before the onset of ischemia, due to the presence of vascular structures within the graft (Mani et al, ). As a result, VNGs are considered to be superior to NVNGs and have been successfully used in several clinical cases (Shibata et al, , Rose and Kowalski, , Restrepo et al, , Koshima and Harii, ).…”
Section: Vascularized Nerve Graftsmentioning
confidence: 99%